Highly Stable Fe3O4/C Composite: A Candidate Material for All Solid-State Lithium-Ion Batteries. Issue 7 (8th April 2020) - Maroni, F.; Bruni, P.; Suzuki, N.; Aihara, Y.; Gabrielli, S.; Carbonari, G.; Agostini, M.; Branchi, M.; Ferrari, S.; Navarra, M. A.; Brutti, S.; Matic, A.; et al.
Abstract : Fe3 O4 nanoparticles synthesized by a base catalyzed method are tested in an All-Solid-State (ASLB) battery using a sulfide electrolyte. The pristine nanoparticles were morphologically characterized showing an average size of 12 nm. The evaluation of the electrochemical properties shows high specific capacity values of 506 mAhg −1 after 350 cycles at a specific current of 250 mAg −1, with very high stability and coulombic efficiency.